Penggunaan Big Data Dalam Mengungkap Kasus Kejahatan Judi Online di Polrestabes Medan - Tobing, Michael Yusuf; Markus Aruan, Miquel Joan; Pakpahan, Kartina (Journal of Economic and Business Law Review, 2023)
One of the important benefits of Big Data and Computing Technology in criminal justice is that it is now easier to store and access records. Thanks to things like social media, people save more than usual. It is likely that the physical copies of the old photos are gone or destroyed, but many people have already posted them on Facebook. A criminal may post an incident, photo, or event on social media that can be traced to reveal the crime he committed and to punish or possibly release him. . To tackle gambling on the internet, Law no. 11 of 2008 concerning Electronic Information and Transactions. When dealing with "internet gambling" there are still new problems that arise, especially regarding evidence. The problem is, what are the benefits of using Big Data in disclosing crime cases by Police investigators and how to use big data in uncovering online gambling cases at the Medan Police. This paper uses a doctrinal research approach. Research results: The use of Big Data to disclose criminal acts should not neglect the protection of the owner of personal data. Subnit VC Sat.Reskrim Polrestabes Medan does not understand technological developments, so it is difficult to use Big Data in uncovering cases of online gambling. It is recommended that Medan Police Investigators attend information technology training and guidance.